SIMILE AND METAPHOR IN THE NOVEL THE SKY IS FALLING - Ayu Talia Meranggi; Dewa Ayu Devi Maharani Santika; WAYAN JUNIARTHA (IJELAL (International Journal of English Learning and Applied Linguistics), 2021)
This study entitled ”Simile and Metaphor in The Novel The Sky is Falling”. Figurative language is commonly found in a literary work, such as a novel. From several types of Figurative language, Simile and Metaphor are the commonly appear. This study aims to analyze simile and metaphor as the types of figurative language within The Sky is Falling novel. This research uses a desriptive qualitative method to describe the types found and the meaning contained in the sentences of the novel. This article uses theory from Knickerbocker and Reninger (1963) to explain the types of figurative language. In general, the results of this study found Simile with 8 data and Metaphor with 4 data. The dominant of the two types figurative language is Simile. This article aims to add insight in the public in order to understand to analyze the sentences of the novel and understand the meaning of novel.